Assessment of Women’s Knowledge Concerning Hydatidiform Mole at Maternity Hospitals in Baghdad City - Fatima Fadel Benyian (Institute of Medico-legal Publications Pvt Ltd, 2020)
Hydatidiform mole results from abnormal fertilization. It is the most common disorder of gestationaltrophoblastic diseases can be partial or complete. Early detection of molar pregnancy and monitoring canreduce complication particularly coriocarcinoma. The fetus typically dies, and a miscarriage often occurs.Objectives: To assess women’s knowledge concerning Hydatitiform mole and find out the associationbetween women’s knowledge with their study variables.Methods: Descriptive study was conducted from November 2019 to February 2020 at maternity hospitalsin Baghdad city. Non probability (purposive sample) was used to collect the data from (100) women whoattending outpatient clinics at maternity hospitals. A questionnaire was constructed about knowledgeassessment tool were designed and prepared by the researcher. A pilot-test is conducted in order to determinethe reliability of the questionnaire in a sample of (20) women who were excluded from the study sample.Data was analyzed through the use of SPSS version 20.Results: The main results revealed that the highest percentage (41.6%) of women’s age was (20-29) years.More than half of them (60 %) are graduated from Secondary Nursing School. They have inadequateknowledge. There are no statistical significant differences between level of knowledge and women’s age oreducational level.Conclusion: This study shows that the knowledge of study sample concerning Hydatitiform mole wasinadequate.Recommendations: It is important to design a booklet or pamphlet about Hydatitiform mole risk factors,signs and symptoms, screening, to reach for all women over the country in order to early detection andprevention.